Citraan Penglihatan Pada Antologi Puisi Nono Warnono “Kidung Langit” - Widiarti, Melia; Nurhadi, Didik; Pratita, Ina Ika (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study examines visual imagery in Nono Warnono's poetry anthology